2014
DOI: 10.1103/physrevlett.113.126801
|View full text |Cite
|
Sign up to set email alerts
|

Limitations to Carrier Mobility and Phase-Coherent Transport in Bilayer Graphene

Abstract: We present transport measurements on high-mobility bilayer graphene fully encapsulated in hexagonal boron nitride. We show two terminal quantum Hall effect measurements which exhibit full symmetry broken Landau levels at low magnetic fields. From weak localization measurements, we extract gate-tunable phase coherence times τ φ as well as the inter-and intra-valley scattering times τi and τ * . While τ φ is in qualitative agreement with an electron-electron interaction mediated dephasing mechanism, electron spi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
69
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 43 publications
9
69
1
Order By: Relevance
“…3e) preventing a more precise estimation. Such a large length scale agrees reasonably well with recent study on inter-valley scattering 21,22 , and is also consistent with the areal density of atomic defects (12.05 m -2 ) found in Kish graphite 23 , which is the same type of specimen used in this study.The observation of a giant nonlocal response in the middle of the energy gap in insulating BLG was unexpected. Although midgap helical edge sates in 2D quantum spin Hall systems can support long-range nonlocal conduction [24][25][26] , such spin helical edge states did not exist in our study because BLG is topologically trivial.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…3e) preventing a more precise estimation. Such a large length scale agrees reasonably well with recent study on inter-valley scattering 21,22 , and is also consistent with the areal density of atomic defects (12.05 m -2 ) found in Kish graphite 23 , which is the same type of specimen used in this study.The observation of a giant nonlocal response in the middle of the energy gap in insulating BLG was unexpected. Although midgap helical edge sates in 2D quantum spin Hall systems can support long-range nonlocal conduction [24][25][26] , such spin helical edge states did not exist in our study because BLG is topologically trivial.…”
supporting
confidence: 79%
“…The valley current in BLG decreases through intervalley scattering, which requires a large momentum transfer (e.g., by atomic scale disorders). Such disorders are found to be Page 8 of 16 extremely rare in cleaved BLG crystals 19,20 , implying a large valley diffusion length 21,22 . In the present study, an appreciable nonlocal signal was observed in samples up to 10 m long.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, Rj of the kink states ranges from 40 to 100 kΩ, which corresponds to a mean free path (MFP) of k = 70-200 nm using the Landauer-Büttiker formula = 0 (1 + / k ) (1), where R0 = h/4e 2 = 6.5 kΩ is the ballistic resistance limit of the 4-fold degenerate kink states and L = 1 m is the junction length in device 1 24 . Although a small contact resistance (several kΩ) may originate from the electrode/kink interface (see Supplementary Section 5), the large value of Rj indicates significant backscattering, i.e.…”
mentioning
confidence: 99%
“…The phase coherence length at T = 1.7 K is estimated to be on the order of the device size, but it falls off with 1/T . 16 The above discussed oscillations can be reproduced by transport calculations for an ideal SLG p-n junction at an intermediate magnetic field B, based on the scalable tight-binding model 17 . The ideal junction is modeled by connecting two semi-infinite graphene ribbons (oriented along armchair) with their carrier densities given by n L in the far left and n R in the far right.…”
mentioning
confidence: 91%